The Influence of Adhesive Curing Mode (Light vs. Dual) on the Microtensile Bond Strength of CAD/CAM Composite Blocks to Human Dentin: (In-Vitro Study) - Hesham, Amr; Kabil, Shadwa Hatem; Haridy, Mohamed Fouad (Journal of Neonatal Surgery, 2025)
Aim: To evaluate the effect of curing mode of adhesive (Light vs. Dual) on micro tensile bond strength (TBS) of CAD/CAM composite blocks to dentin. Methods and Materials: Total number of eighteen posterior molars were randomly assigned into 2 groups (n=9 per each group) according to the investigated variable the types of adhesive systems (light and dual cured). Each tooth placed in self-cured acrylic resin and then sectioned parallel to expose dentin. Following 2 groups were: -A) light cured adhesive (one coat universal adhesive), B) Dual cured adhesive (one coat universal adhesive with its activator). Composite blocks (Brilliant, Coltène) milled into 5 mm diameter blocks then cemented to teeth using dual cured (DUO-LINK: Dual cure resin cement). All specimens stored in distilled water at room temperature for 24 hours before thermo-cycling. All specimens thermal cycled in distilled water for 5,000 cycles at 5±2°C/55±2°C. After the approval of the Scientific Research Ethics Committee, Faculty of Dentistry, British University in Egypt. Results: Group I [light cured one coat 7 universal adhesive] (19.83 ± 1.25) demonstrated significantly higher micro tensile bond strength than Group II [Dual cured adhesive one coat 7 universal adhesive] (11.78 ± 1.25). Conclusions: Regarding of curing mode of adhesive system, light cured adhesives outperformed dual cured adhesives in bond strength. are clinically reliable and can be chosen based on workflow needs without compromising restoration quality